Network disruption detected in UA (Ukraine) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Ukraine. Data sourced from CensoredPlanet, IODA.
Network Disruption Incident ID: UA-2026-0001. Severity: critical. Confidence: 70%